Understanding public concern about climate change in Europe, 2008–2017: the influence of economic factors and right-wing populism. (16th March 2021) - Duijndam, Sem; van Beukering, Pieter
ABSTRACT: European survey data shows strong temporal fluctuations in climate change concern within European countries and large differences in concern between these countries. However, there is as yet no comprehensive understanding of what drives these longitudinal and cross-sectional patterns. To fill this knowledge gap, this study analyzes data of over 155, 000 survey respondents from 28 European countries over the period 2008–2017. This study is the first to apply within-between random effects models to simultaneously analyze longitudinal and cross-sectional determinants of climate change concern, and examine if and how the influence of these determinants has changed over time. Substantively, it researches the nexus between climate change and two other crises that have captured the imagination of European publics over the studied period: the liberal democracy crisis and the economic crisis. The former is characterized by the rise of right-wing populist parties in Europe. Right-wing populism is often at odds with climate change policies, and its rise in popularity could have undermined public concern about climate change. We find only a weak negative longitudinal relationship between such concern and the popularity of right-wing populist parties, and no significant cross-sectional relationship. We find that economic performance is strongly positively associated with concern, with GDP per capita being most important for explaining cross-country differences in concern, and deviations in unemployment being most important for explaining longitudinal within-country change. However, this negative longitudinal relationship with unemployment weakens considerably over time, illustrating the importance of including dynamic effects in modeling efforts to generate more reliable results. Key policy insights The percentage of European respondents mentioning climate change as one of the most serious world problems declined from 65% in 2008 to 43% in 2017. This study does not find a strong direct relationship between the rise of climate skeptic right-wing populist parties and public concern about climate change. Economic factors are important predictors of climate change concern, with GDP per capita being the dominant driver of between-country differences, and unemployment the dominant within-country predictor. The marginal impact of unemployment was much stronger during, rather than after, the economic crisis.